Detection and formation mechanisms of secondary nanoplastic released from drinking water bottles. (15th August 2022) - Winkler, Anna; Fumagalli, Francesco; Cella, Claudia; Gilliland, Douglas; Tremolada, Paolo; Valsesia, Andrea
Highlights: We describe an analytical method to detect release of nanoplastics in water matrix. We measured released nanoparticles from water bottles under realistic use condition. Quantitative studies of nanoplastics release are essential for hazards assessment. We observe that mechanical stress alters structural characteristics of nanoplastics. Understanding material degradation processes is crucial for analyzing nanoplastics. Abstract: Since nanoplastics are currently considered potentially hazardous to the environment and human health, reliability of studies on nanoplastic exposure becomes crucial. However, analytical challenges limit our understanding of their formation and detection, thus hampering their biological interactions assessment. Here we provide a combined approach to quantitatively and qualitatively detect the release of nanoplastics in water matrix and, in particular, to measure direct exposure of consumers by simulated use of drinking water plastic bottles. We measured that the polyethylene sealing of the bottles released particles with a size distribution ranging from few hundreds nanometers up to about one micron and estimated a mass release in the order of few tenths of nanograms per opening/closing cycle. We observe that mechanical stress alters the physical-chemical characteristics of the generated secondary nanoplastics and degrades the material properties compared to the original bulk source, thus complicating their spectroscopic chemical identification. Our findings demonstrate that understanding material degradation processes is therefore crucial for identifying and quantifying nanoplastics in real samples. Moreover, methods allowing quantitative studies on the release of nanoplastic as a source of exposure are considered essential for proper assessment of their potential health hazards and to promote improvements in consumer products plastic packaging design.